Inwards Interweaving of Polymeric Layers within Hydrogels: Assembly of Spherical Multi‐Shells with Discrete Porosity Differences. (27th May 2013) - Pan, Houwen Matthew; Beyer, Sebastian; Zhu, Qingdi; Trau, Dieter
Abstract The unique inwards interweaving morphology of polyamines and polyacids within agarose hydrogels that leads to the formation of striated shells with different porosities within the spherical scaffold is reported. Microcompartments with sophisticated structures are commonly used in drug delivery, tissue engineering, and other biomedical applications. However, a method capable of producing well‐defined, multiporous shells within a single compartment is still lacking. By the alternating deposition of polyallylamine (PA) and polystyrenesulfonic acid (PSS) in 1‐butanol, at equal mass ratios, multiple levels of porosity are generated within an agarose microsphere. Each level of porosity is represented by a well‐defined, concentric shell of interweaving PA and PSS layers. The number, thickness, and porosity of the striated shells can be easily controlled by varying the number of PA/PSS bilayers and the polymer concentration, respectively. The feasibility of utilizing this morphology for the assembly of a multi‐shell porous spherical scaffold is validated by trapping different molecular weight dextrans within different regions of porosity. The unique interaction of polyacids and polyamines in hydrogels represents a facile and inexpensive approach to the development of intricate scaffold architectures.